The global threat of Zika virus to pregnancy: epidemiology, clinical perspectives, mechanisms, and impact. Issue 1 (December 2016) - Boeuf, Phillipe; Drummer, Heidi; Richards, Jack; Scoullar, Michelle; Beeson, James
Abstract Zika virus (ZIKV) is a mosquito-borne flavivirus that has newly emerged as a significant global threat, especially to pregnancy. Recent major outbreaks in the Pacific and in Central and South America have been associated with an increased incidence of microcephaly and other abnormalities of the central nervous system in neonates. The causal link between ZIKV infection during pregnancy and microcephaly is now strongly supported. Over 2 billion people live in regions conducive to ZIKV transmission, with ~4 million infections in the Americas predicted for 2016. Given the scale of the current pandemic and the serious and long-term consequences of infection during pregnancy, the impact of ZIKV on health services and affected communities could be enormous. This further highlights the need for a rapid global public health and research response to ZIKV to limit and prevent its impact through the development of therapeutics, vaccines, and improved diagnostics. Here we review the epidemiology of ZIKV; the threat to pregnancy; the clinical consequences and broader impact of ZIKV infections; and the virus biology underpinning new interventions, diagnostics, and insights into the mechanisms of disease.